“El caso Berciani” de Alan Pauls: un viaje a los bajos fondos - Rubio Gijón, Pablo (Acta Hispanica, 2016)
“El caso Berciani” (1992) relates tothe genre of detective and mystery fiction byparody and distortion. Alan Pauls (Buenos Aires,1959) explores the relation between order andabjection. In so doing, “El caso Berciani” becomesa thorough reflection on the failure ofmodernization. This article explores how thisshort story uses detective fiction to elaborate onknowledge and interpretation, and urban dystopiasand social tensions.